Analisis Hubungan Kemampuan Berpikir Kreatif dan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 26 Makassar - Nirwana Nirwana; Nurhayani H. Muhiddin; Salma Samputri (Universitas Negeri Makassar, 2025)
This study aims to determine 1) the level of creative thinking ability of class VIII students of SMP Negeri 26 Makassar. 2) the level of learning outcomes of class VIII students of SMP Negeri 26 Makassar. 3) the relationship between the ability to think creatively and the learning outcomes of class VIII students at SMP Negeri 26 Makassar. The type of research used is survey research using a correlational design. The population in this study were class VIII students at SMP Negeri 26 Makassar for the academic year 2022/2023, totaling 250 students. Samples were taken using the slovin formula with simple random sampling technique of 71 students. The instrument used in this study was a creative thinking ability test instrument in the form of an essay consisting of 10 questions, and existing learning outcome scores given by science subject educators at the school. Data were analyzed with descriptive statistics and inferential statistics. The results of descriptive statistical analysis show that the level of creative thinking ability is in the moderately creative category with a value of 41,48 and learning outcomes are in the moderate category with a value of 52,00. The results of the inferential analysis show that there is a relationship between creative thinking abilities and learning outcomes with a Pearson Correlation of 0.57 which indicates that there is a moderate relationship.